Assessing the effect of IFT and exercise therapy on OA knee. - Craig Dyson (2010)
Background: Osteoarthritis (OA) is a chronic, degenerative disease that mainly affects weight bearing joints and is the most common disease of the musculoskeletal system (Naredo et al, 2005). It is estimated to affect It is thought that as many as 10% of people over the age of 65 in the US suffer with the disease (Felson, 1982) leading to an economical cost of around {dollar}86 billion (Abell 2005). Therefore the best ways to manage the condition are important to keep the physical functioning of the individual sufferer high and the cost to the economy low. Aims: The aim of this MPhil thesis is to explore and present the current research surrounding the use of exercise therapy and Interferential Therapy (IFT) in the use of Osteo-arthritis (OA) of the knee. The thesis also aims to test whether the combination of the two treatment methods is more effective than either treatment used in isolation. Methods: The current research on the use of IFT and exercise therapy will be presented as a review of the defined area. The clinical assessment of the treatment modalities will be tested in a pilot study that is presented as a single-blind randomised controlled trial. Results: The review chapter of the study reports that there is a perceived benefit of exercise therapy and IFT in the treatment of OA knee. However, the types of exercise and frequency needed have yet to be clarified. The use of IFT in the treatment of OA knee has yet to be researched in any great depth, although previous studies do suggest that it may have a beneficial effect even though the optimum settings have yet to be clarified. In the study presented it was found that exercise therapy produced the best results when compared with IFT in isolation. However, the combination of IFT and exercise therapy did also produce significant improvements. Conclusion: The thesis highlights the need for further research into the areas of IFT and exercise therapy as treatments for knee OA. The lack of uniformity in both areas of research makes comparison of treatment methods difficult, and as a result it is difficult to draw any definite conclusions, although exercise therapy does appear to be successful in the treatment of knee OA. The pilot study as part of the thesis demonstrates that the methodology used is a robust and innovative way of assessing the effect of IFT and exercise therapy in the clinical environment, and could be used as part of a larger scale multi-centre trial. The results of the study chapter appeared to demonstrate that the combination of treatments outlined above was the most effective in the treatment of knee OA. Further studies are needed to assess whether any further improvements of the combination treatments are cost-effective.